Officer strategies for managing interactions during police stops. (2nd January 2020) - Quinton, Paul
ABSTRACT: This paper draws on ethnographic research carried out in England and Wales soon after the Lawrence Inquiry to present an historical analysis of the strategies used by officers to manage interactions with suspects during police stops. The paper uses Goffman's conceptual apparatus to explore how officers established order during interactions, monitored suspects' demeanour closely to decide what was going on and how to proceed, and carefully controlled information to stage-manage encounters. By way of comparison, the paper describes interactions with known offenders who were stopped more regularly. The conclusions emphasise how officers exerted control during interactions through subtle uses of power, and discusses the policy implications.